The Right to Abortion in Tunisia after the Revolution of 2011: Legal, Medical, and Social Arrangements as Seen through Seven Abortion Stories - Irene Maffi; Malika Affes (Harvard FXB Center for Health and Human Rights, 2019)
In this article, we explore the effects that Tunisia's post-revolutionary democratization process has had on the right to abortion, drawing on ethnographic material, interviews, and medical files that we collected between 2013 and 2017, as well as the professional experience of one of us. We show that despite the existence of a relatively liberal abortion law for more than 40 years, women in Tunisia have trouble getting abortion care for economic and organizational but also ideological and political reasons. The existence of the abortion law constitutes but one factor among many others that determine women's ability to access abortion services; medical practices and women's abortion itineraries are caught up within complex arrangements that entail multiple socioeconomic and cultural factors, political transformations, the variability of rules in medical and administrative institutions, and contradictory interpretations of the legal apparatus. Examining the abortion itineraries of seven women we met in a large hospital in Tunis, we argue that these abortion itineraries shed light on the ordinary constraints experienced by poor Tunisian women who cannot afford to turn to the private sector. We maintain that attitudes toward the right to abortion in post-revolutionary Tunisia are problematic and that the democratization of local society has brought about unexpected consequences that do not extend but rather reduce women's rights in the domain of sexual and reproductive health.